PENINGKATAN KETERAMPILAN HIDUP MELALUI PROGRAM LITERASI FUNGSIONAL MODEL UNESCO - Jacobus Rico Kuntag; Survey Sijabat; Nurul Istiqomah; Yuni Ratna Purwaningsih; Arin Mantara Anggawirya; Rosalia Floriani; Evelin Giovani; Bhujangga Ayu Putu Priyudahari (Nusantara Hasana Journal, 2026)
This community service program aimed to improve the life skills of Indigenous Papuan students through the UNESCO Functional Literacy Model. The activity was conducted at the Yalimo Student Dormitory, located on Jalan Onggatmit, Merauke, involving 11 participants from Yalimo Regency, Papua Highlands Province, consisting of 3 senior high school students and 8 Indigenous Papuan university students. The program was designed in response to the need for literacy development that goes beyond reading and writing skills and includes the ability to understand information, write for practical purposes, perform basic numeracy, manage oneself, use technology appropriately, and develop work readiness. The activity employed a participatory-educative approach through training, discussion, simulation, hands-on practice, mentoring, and reflection. The program involved 3 instructors with academic backgrounds in economics, English literature, and computer studies, supported by 5 facilitators. The program materials covered functional reading literacy, functional writing literacy, numeracy literacy, life literacy, digital literacy, work-related literacy, learning motivation, and self-development. Evaluation was conducted through pre-tests, post-tests, observation, worksheets, and participant reflection. Participants demonstrated progress in understanding written information, writing simple practical texts, calculating transactions, preparing learning plans, recognizing personal potential, and understanding the importance of literacy in daily life.